Motives And Causes of Migration of Health Workers for Work Abroad - Paulina SROVNALIKOVA; Vaida BACIULIENE; Valentinas NAVICKAS (Communications of International Proceedings, 2021)
Migration flows from one country to other cause inevitable changes in both the origin country and the host country. Migration itself should not be seen as a one-sided process. Researchers distinguish several types of migration flows: "carousels", "step" and "cascade". Emerging "chain" migration flows are also observed, with workers following one another, often by employment agencies. Pull and push factors are distinguished in migration theory. The main motivation for health workers to immigrate to another country is higher pay, but migration flows are not driven by push but by pull factors, especially the resulting shortage of health workers, which can be regulated by the states.
Keywords: Migration; Health Workers; Motives and Causes; Pull and Push Factors.